COMPREHENSIVE EXAMINATION OF ANIMAL HUSBANDRY ON A GLOBAL SCALE, EMPHASIZING THE CONTEXT OF INDIA (International Journal of Food and Nutritional Sciences, 2022)
Livestock and animal husbandry continue to play a crucial role in sustaining rurallivelihoods, particularly in the Least Developed Countries (LDCs) and developingnations such as India. This sector exhibits substantial growth potential globally andserves as a major source of gainful employment worldwide. Against this backdrop, thepresent study aims to assess the performance of animal husbandry from a globalperspective.The primary objectives of the study include examining the positioning of countries inthe global livestock population, scrutinizing the cattle livestock population in selectednations, evaluating trends in the overall global livestock population, and analyzing thetrajectory of milk production in both Asian countries and worldwide. The investigationrelies on secondary data extracted from various national and international reports, withthe study period spanning from 2007 to 2017.